Komparasi Keragaman Jenis Liana di Desa Uemea Kabupaten Banggai dengan Desa Wajageseng Kabupaten Lombok Tengah - Latifa, Gina; Sukenti, Kurniasih; Iqbal, Moh. (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2024)
Lianas are vines or climb on other plants to get sunlight. This study aims to provide additional information related to liana diversity in Uemea Village, which is one of the village forests in Toili District, Banggai Regency, Central Sulawesi, and Wajageseng Village, which is located in Lombok and directly adjacent to Setiling Resort, Mount Rinjani National Park. The method used was exploration by looking at aspects of habitat rich in tall trees that allow lianas to grow and reproduce fertilely and with quite diverse liana growth, then observed to see and determine the same type of liana. The results showed that in Uemea Village 25 species of lianas belonging to 14 families were found, while in Wajageseng Village 18 species of lianas belonging to 11 families were found. There is a similarity of liana species between Uemea Village and Wajageseng Village, namely Mikania micrantha Kunth. The most common family found in Uemea Village is Araceae due to low air temperature and humidity with an area under water management, causing the area to be humid while in Wajageseng Village, the most common families found are Piperaceae and Vitaceae because they tend to have a temperate climate.